On adaptive estimation in partial linear models - Georgi Golubev; Wolfgang Härdle (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 2000)
We consider a problem of estimation of parametric component in a partial linear model. Suppose that a finite set E of linear estimators is given. Our goal is to mimic the estimator in E that has the smallest risk. Using a second order expansion of the risk of linear estimators we propose a practically feasible adaptive procedure for choke of smoothing parameters based on the principle of unbiased risk estimation.
urn:nbn:de:kobv:11-10047279
Keywords: 330